Reduced participation in traditional games: a limiting factor for aerobic capacity in adolescents aged 11 to 15 years - Iza Recalde, David; Meza Elizalde, Jason (Revista Ecos de la Academia, 2023)
The present research work focuses on the possibility of using traditional games as an alternative educational tool to improve aerobic capacity and prevent health problems derived from sedentary lifestyles. The objective of the present study was to evaluate the effectiveness of the incorporation of traditional games as an alternative to improve the aerobic capacity in students of the eighth and ninth year of general basic education of the "A", "B" and "C" parallels of the "Gabriela Mistral" Educational Unit, who are between 11 and 15 years old. The research methodology used was quantitative, descriptive in scope and non-experimental in design. In this framework, a questionnaire was applied to collect information about the students' knowledge of traditional games. In addition, the Ruffier-Dickson test was used to obtain data to assess the level of aerobic capacity of the students. The study summarises the importance of traditional games in physical activity and cultural preservation and shows the importance of regular monitoring of aerobic capacity to prevent future cardiovascular problems affecting students' daily lives.
Keywords: traditional games; aerobic capacity; physical education; EGB; Ruffier-Dickson test